Neurological consequences of SARS-CoV-2 infections in the pediatric population - Casabianca, Manon; Caula, Caroline; Titomanlio, Luigi; Lenglart, Léa (Frontiers in Pediatrics, 2023)
COVID-19 in the pediatric population is mostly asymptomatic. However, 1 out of 5 children presents non-specific neurologic symptoms such as headache, weakness, or myalgia. Furthermore, rarer forms of neurological diseases are increasingly being described in association to a SARS-CoV-2 infection. Encephalitis, stroke, cranial nerves impairment, Guillain-Barré syndrome or acute transverse myelitis have been reported and account for around 1% of pediatric COVID-19 cases. Some of these pathologies may occur during or after the SARS-CoV-2 infection. The pathophysiological mechanisms range from direct invasion of the central nervous system (CNS) by SARS-CoV-2 itself to postinfectious immune-mediated CNS inflammation. In most cases, patients presenting neurological pathologies related to SARS-CoV-2 infection are at greater risk of life-threatening complications and should be closely monitored. Further studies are needed to acknowledge the potential long-term neurodevelopmental consequences of the infection.